Chapter Le libertà delle città dei regni. Mezzogiorno italiano ed Europa (secoli XIII-XV) - TERENZI, Pierluigi (Firenze University Press, 2025)
The relationship between cities and sovereigns in the kingdoms of southern Italy is investigated by the author from a European perspective, highlighting how libertas was equivalent to the submission of communities to monarchical power and the absence of lordly domination, making subjection the essential condition for obtain it or keep it under the guarantee of the sovereign; and how anti-monarchical revolts, both those connected with taxation and those intended to replace the dynasty, were bearers of a generic notion of freedom. The libertates of which the monarch was the guarantor were not only made up of the immunities and rights that contributed to defining the political space of the cities within the kingdom but founded the relationship of legitimation between the sovereigns and the city ruling groups that carried out public functions in his name.